The impact of time-updated resting heart rate on cause-specific mortality in a random middle-aged male population: a lifetime follow-up. (25th November 2020) - Cui, X.T; Mandalenakis, Z; Thunstrom, E; Fu, M; Svardsudd, K; Hansson, P.O
Abstract: Background: High resting heart rate (RHR) is associated with increased adverse events. However, the long-term prognostic value in a general population is unclear. We aimed at investigating the impact of RHR, based on baseline as well as time-updated, on mortality in a middle-aged men cohort. Methods: A random population sample of 852 men, all born in 1913 was followed from age 50 until age 98 with repeated examinations including RHR during 48 years. The impact of baseline and time-updated RHR on cause-specific mortality was assessed using Cox proportional hazards models and cubic spline models. Results: Baseline RHR ≥90 beats per minute (bpm) was associated with higher all-cause mortality as compared to RHR 60–70 bpm (hazard ratio [HR] 1.60, 95% confidence interval [CI] 1.17–2.19, P=0.003), but not with cardiovascular (CV) mortality. A time-updated RHR <60 bpm (HR 1.41, 95% CI 1.07–1.85, P=0.014) and a time-updated RHR of 70–80 bpm (HR 1.34, 95% CI 1.02–1.75, P=0.036) were both associated with higher CV mortality as compared with the RHR of 60–70 bpm after multivariable adjustment. Analyses using cubic spline models confirmed that the association of time-updated RHR with all-cause and CV mortality complied with a U-shaped curve with 60 bpm as a reference. Conclusions: In this middle-aged men cohort, a time-updated RHR at 60–70 bpm was associated with lowest CV mortality, suggesting that time-updated RHR could be a useful long-term prognostic index in the general population. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): In recent years, funding has been received from the Swedish state under the agreement between the Swedish government and the county councils relating to the economic support of research and education under the ALF agreement (ALFGBG-721351).